Investment in Public Sport and Leisure Policies in the City of Rio de Janeiro - Edimilson Santos dos Santos (Universidade Salgado de Oliveira, 2020)
The present descriptive and exploratory study had as a main goal to analyze public investment on the Sport and Leisure Function (FDL) on the part of municipalities in the state of Rio de Janeiro. The database was prepared based on investments from 2002 to 2011 by population size. The displacement of political authority concerning the implementation of sport and leisure public policies explains, to a reasonable extent, results referring to adhesion and amount of investment. However, the most important conclusion is that municipalities in the state of Rio de Janeiro do not prefer inaction. They are quite active, despite the inequality in investment capacity, in the implementation of sport and leisure policies.